The Principle of the Verse Segmentation - Adam Kulawik (Annales Universitatis Paedagogicae Cracoviensis. Studia Poetica)
This article is a translation of a part of a collective book published in 1984, which forms the foundations of the prosodic theory of verse, an original research project that was further developed into an independent theory of verse in several books. The paper explores the theoretical framework and principles underlying the segmentation of verse, distinguishing it from prose, argues that traditional verse theory has struggled to define and analyze verse effectively due to its reliance on metrics. The author proposes a redefinition of verse, emphasizing the role of prosodic segmentation, and verse-pause as its foundation.Verse is redefined as a distinct method of text segmentation characterized by arbitrary pauses that create verses. Unlike prose, where segmentation is dictated by syntax and logic, verse segmentation introduces an expressive, nonsyntactical structure motivated by arbitral verse‑pauses. This definition separates the concept of verse from that of literature, of poetry, prose, and artism, allowing for a more flexible and inclusive understanding of the phenomenon of verse.